2013
DOI: 10.3354/meps10284
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal growth, respiration rate and fatty acid composition in the cold-water coral Lophelia pertusa under varying food conditions

Abstract: Reefs of the cold-water coral Lophelia pertusa form biodiversity-rich habitats in the deep ocean, but physiology, reproduction, feeding and growth in this species remain poorly investigated. Food supply to reef sites varies considerably both spatially and temporarily. In this study we investigated the effects of starvation and zooplankton feeding on respiration and growth of L. pertusa. In our first experiment, corals were starved for 6 mo, resulting in a 40% decrease in respiration but no visible effects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 66 publications
9
70
0
Order By: Relevance
“…The concentration of total fatty acids (20 mg g −1 DW tissue with tissue DW contributing 5 % to total DW, as observed in this study), however, was below the range of 55-124 mg g −1 DW tissue reported by Dodds et al (2009) for L. pertusa from Rockall Bank, Mingulay Reef and New England Seamounts. Local differences can be responsible for this discrepancy as Larsson et al (2013a) reported storage fatty acids concentrations of 15 to 19 mg g −1 DW tissue from L. pertusa collected at the Tisler Reef but also the maintenance in aquaria (3 month in this study) might have altered the lipid content (Larsson et al, 2013b).…”
Section: Biochemical Characteristics Of L Pertusamentioning
confidence: 66%
“…The concentration of total fatty acids (20 mg g −1 DW tissue with tissue DW contributing 5 % to total DW, as observed in this study), however, was below the range of 55-124 mg g −1 DW tissue reported by Dodds et al (2009) for L. pertusa from Rockall Bank, Mingulay Reef and New England Seamounts. Local differences can be responsible for this discrepancy as Larsson et al (2013a) reported storage fatty acids concentrations of 15 to 19 mg g −1 DW tissue from L. pertusa collected at the Tisler Reef but also the maintenance in aquaria (3 month in this study) might have altered the lipid content (Larsson et al, 2013b).…”
Section: Biochemical Characteristics Of L Pertusamentioning
confidence: 66%
“…Calculations (Eqns 16-18) revealed that less than 0.5% of energy would be required for calcification in relation to overall respiration in M. oculata (Table 2). Also, for L. pertusa only 3-5% of the available energy is allocated to calcification in comparison to respiration (Larsson et al, 2013), and metabolic carbon contribution to calcification was 1% in relation to that of the tissue pool and respiration for the CWC L. pertusa (Mueller et al, 2014). The relatively low energy requirement for upregulation of Ω a in the calcifying fluid and the maintenance of relatively high calcification rates might explain the observed resistance to ocean acidification.…”
Section: Energy Requirements For Up-regulation Of the Calicoblastic Phmentioning
confidence: 95%
“…Starvation of D. dianthus caused an initial and significant decrease in calcification after 1 week, while starvation for another 2 weeks did not result in further significant reduction of calcification rates (Naumann et al, 2013b). When L. pertusa was provided with various concentrations of food over 15 weeks, only small and non-significant changes in respiration were measured, and no effect on calcification occurred, despite the fact that food supply varied by a factor of 7.5 (Larsson et al, 2013). Also, for M. oculata (this study) the HF regime only affected the first measurements on calcification, which were taken 2 weeks after the respective feeding regimes had been applied, while during later measurements (4-10 weeks), calcification was independent of feeding regime.…”
Section: Effect Of Nutrition On Metabolic Functioningmentioning
confidence: 99%
See 2 more Smart Citations